2004
DOI: 10.1097/01.wcb.0000095798.98378.34
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection after Transient Global Cerebral Ischemia in Wlds Mutant Mice

Abstract: Summary:The Wld s mouse mutant demonstrates a remarkable phenotype of delayed axonal and synaptic degeneration after nerve lesion. In this study, the authors tested the hypothesis that expression of Wld protein is neuroprotective in an in vivo mouse model of global cerebral ischemia. This model is associated with selective neuronal degeneration in specific brain regions such as the caudate nucleus and CA2 hippocampal pyramidal cell layer. The extent of neuronal damage was quantified in Wld s compared to wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…Although the protective effects of Wld S against axonal degeneration have been well documented [13][14][15][16][17], our studies provide evidence that it can protect against STZtriggered pancreatic beta cell death and subsequent diabetic symptoms and pathological events in mice. Wld S is expressed in islets, suggesting a direct protective effect on beta cells.…”
Section: Discussionmentioning
confidence: 78%
“…Although the protective effects of Wld S against axonal degeneration have been well documented [13][14][15][16][17], our studies provide evidence that it can protect against STZtriggered pancreatic beta cell death and subsequent diabetic symptoms and pathological events in mice. Wld S is expressed in islets, suggesting a direct protective effect on beta cells.…”
Section: Discussionmentioning
confidence: 78%
“…The expression of Wld s , Nmnat1, or Nmnat3 in neurons protects against axonal degeneration resulting from damage caused by mechanical, genetic, or chemical injury Wang et al, 2001a,b;Ferri et al, 2003;Samsam et al, 2003;Araki et al, 2004;Gillingwater et al, 2004;Mi et al, 2005;Sasaki et al, 2006;Zhai et al, 2006). The association between mitochondrial dysfunction and axonal degeneration in multiple neurological disorders encouraged us to investigate whether Nmnat expression could protect axons from damage caused by mitochondrial dysfunction.…”
Section: Rotenone Treatment Of Drg Neurons Results In Axonal Degeneramentioning
confidence: 99%
“…Bilateral injuries to the striatum were in particular more frequent than those to the hippocampal CA1 subregion, another vulnerable brain region. Although striatal injury after tGCI has not received much attention, some authors have also reported that striatal neurons are the most vulnerable in C57BL/6 mouse brains after tGCI (Gillingwater et al, 2004;Olsson et al, 2003;Terashima et al, 1998;Yang et al, 1997;Yoshioka et al, 2010). Therefore, a striatal injury model that uses C57BL/6 mice can be appropriate for studying neuronal death after tGCI.…”
Section: Discussionmentioning
confidence: 99%